EXPERIMENTAL STUDY OF HEAT TRANFER AUGMENTATION USING AIR BUBBLE INJECTION AND (Al2O3 /WATER) NANOFLUID FLOW IN DOUBLE PIPE HEAT EXCHANGERS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
In the present work, an experimental study on how to increase the heat transfer coefficient (HTC) in double pipe heat exchanger (DPHE) use of a variety of Al2O3 Nano-dispersion concentrations mixed in water as base fluid with air bubble injection for counter flow arrangement under turbulent flow conditions with (Re) Reynold number range from (6000 t0 45000) . The thermal performance of (DPHE) has been enhanced with the use of two techniques. The first, is represented by adding nanoparticles to hot water (inner pipe) raising the (HTC) inside the inner tube. Increase the volume concentration cause increase in the viscosity of the nanofluid leading to increase in friction factor .Secondly is represented by Air bubble injection in outer pipe with cold water to enhance the (HTC). The mobility of air bubbles inside the water from down to up by the force of the buoyancy, and the movement of these air bubbles results in significant mixture and turbulence within the water. The variations of number of thermal units (NTU), exergy loss, dimensionless exergy and (Nu) are evaluated. The investigated parameters were cold water volume flow rates (8, 10, 12 and14) l/min, flow in outer tube. Also, three different volume flow rates of air (12, 16 and 20) l/min mixed with water in outer tube. The volume flow rates of hot water remains constant at (8 l/min) flow in inner pipe with three volumetric concentrations of given nanofluid. The results showed that the air bubble injection throughout the tube gave maximum enhancement in heat transfer characteristics followed by the no air bubble injection. Since the enhancement in heat transfer characteristics varies linearly with the volumetric concentration of Nanofluids, Nanofluids with 0.3% of Al2O3 nanoparticles gave more enhancements in (HTC) than the case without nanofluid. The Nusselt number increased about (8% - 45%).